A Study on Xi Jinping Thought on Diplomacy as the Theoretical Basis of China’s Multipolar World Vision - CAKILCIp, Ulas Birkan (sourcecoder, 2025)
This article examines the implications of Xi Jinping Thought for diplomacy as the theoretical foundation of China’s vision of a multipolar world. Xi Jinping Thought adapts Marxism to the Chinese context, combining China’s modernization process in line with socialism and its global vision. Diplomacy serves China’s national goals and contributes to the development of a multilateral international order. This thought aims to promote multipolarity in the face of hegemony. The article analyzes the dimensions of Xi Jinping Thought through a qualitative analysis and assesses how it has shaped China’s foreign policy. Xi Jinping Thought underpins China’s major-country diplomacy and consolidates China’s role in global governance by combining socialism and global vision. Moreover, by taking a more active role on the world stage, China aims to build a shared future for mankind, combating hegemonic structures, and pursuing a global order based on justice and equality. Promoting China’s vision of a multipolar world requires developing foreign policy strategies focused on greater global cooperation and equality. Furthermore, the integration of Xi Jinping Thought into a broader international framework can further strengthen China’s global role.